Varietal Improvement of Wheat for Eastern Terai of Nepal - Prasai, Hari Kumar (International Journal of Applied Sciences and Biotechnology, 2017)
The regional varietal experiments of wheat were composed by selecting promising genotypes from coordinated varietal trial. Both early and late sown experiments of wheat regional varietal trial (RVT) were seeded in Regional Agricultural Research Station, Tarahara, Sunsari, Nepal in 2014 and 2015. Late sown experiment was seeded after 15 days of early seeding experiment to identify suitable genotypes for delay seeding condition. Amongst the tested genotypes in RVT early of 2014 and 2015, the highest grain yield was produced by BL 3555 (3351 kg/ha) and BL 4018 (3309 kg/ha). Similarly BL 4012, BL 3978, BL 3264 and BL 4406 genotypes also recorded 12-18 percent higher grain yield than the yield of standard check variety, Aditya. All tested characters except spikes/m2 included in over year analysis of RVT early was found significantly different due to genotypes. Similarly out of the tested genotypes in RVT (late) of 2014 and 2015, NL 1177 (2933 kg/ha) and BL 3555 (2764 kg/ha) were found high yielding genotypes in combined analysis over year and grain yield of other tested genotypes was observed at par with check variety. Days to heading, maturity, plant height and yrain yield of RVT (late sown) experiment were observed significantly different due to genotypes in over year analysis. Int J Appl Sci Biotechnol, Vol 4(4): 519-524